The effect of quercetin on erythrocyte glucose-6-phosphate dehydrogenase enzyme activity in ethanol treated rats - Vurmaz, A.; Kahraman, A.; Koken, T.; Serteser, M. (WILEY-BLACKWELL, 2016)
41st FEBS Congress on Molecular and Systems Biology for a Better Life, Kusadasi, TURKEY, SEP 03-08, 2016
Keywords: Erythrocyte; ethanol; G6PD; oxidative stress; quercetin